Development of LKPD with Ethnoscience Content of Lombok Island to Train Science Literacy Skills in Learning IPAS Class V SDN 27 Ampenan - Ningsih, Ratna; Dewi, Nurul Kemala; Erfan, Muhammad; Hasnawati (Mataram University, 2024)
This research aims to produce teaching materials LKPD with ethnoscience content of Lombok Island to train science literacy skills in IPAS learning class V SDN 27 Ampenan which is valid, practical, and effective. The type of research used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were 20 students from the VA SDN 27 Ampenan class. The data collection instruments used were media and material expert validation questionnaire sheets, teacher and student response questionnaire sheets, and science literacy ability test sheets. The results showed the validity of LKPD obtained a percentage value of 89.96% with very valid criteria. In the small group trial with 8 students, the LKPD obtained a percentage value of 95% with very practical criteria by teachers and 97.11% with very practical criteria by students. In the large group trial with 20 students, the LKPD obtained a percentage value of 96% with very practical criteria by teachers and 92.92% with very practical criteria by students. The completeness of the learning outcomes of science literacy skills was 100% with a very effective category, the achievement of science literacy indicators was 88.25% with a very good category, and the average N-Gain was 0.77 with a high category. Based on these results, the LKPD can be declared valid, practical, and effective as teaching materials to train science literacy skills in class V SDN 27 Ampenan.